NAGORNO-KARABAKH: SEPARATISM AND ELECTORAL LEGITIMACY - ALIEV, Namig (CENTRAL ASIA AND THE CAUCASUS, 2005)
The conflict known throughout the world as the “Nagorno-Karabakh” conflict arose during the disintegration of the U.S.S.R. The situation that had taken shape in the Soviet Un-ion at that time was conducive to the emergence of this conflict, while the confrontation over Nagorno-Karabakh, encouraged by the country’s authorities led by Mikhail Gorbachev, served as a catalyst of centrifugal processes, triggering off numerous ethnic and territorial conflicts in the post-Soviet space and transforming the evolutionary process of the U.S.S.R.’s disintegration into a revolutionary breakup. The active phase of the conflict started in February 1988, when the separatist forces of the Nagorno-Karabakh Autonomous Region (NKAR) of the Azerbaijan Republic, instigated by the Republic of Armenia, began to organize rallies, strikes and other civil disobedience actions, seeking a secession of the region from the Azerbaijan Republic and its incorporation into the Re-public of Armenia. Ethnic cleansing of Azeris started in that Union republic of the U.S.S.R. and in the territory of Nagorno-Karabakh, with the creation of monoethnic Armenian areas.1 As a result of the first stage of the conflict, the parliament of the Republic of Armenia took a decision to incorporate the NKAR into the Republic of Armenia, whereas the Azerbaijan Republic abolished the NKAR and extended its uniform administrative-territorial division to that territory.2The conflict moved into the phase of armed hostilities in late 1991 and early 1992, when the U.S.S.R. had ceased to exist and the last legal and organizational (except international legal) barriers to the forcible annexation of Nagorno-Karabakh by the Republic of Armenia had been removed.